Surface polarity estimation of metal-organic frameworks using liquid-phase mixture adsorption - Sin, Maria; Kutzscher, Christel; Senkovska, Irena; Ben, Teng; Qiu, Shilun; Kaskel, Stefan; Brunner, Eike (Microporous and Mesoporous Materials, 2017)
A new methodology for surface polarity screening of MOFs is proposed based on quantitative 1H NMR spectroscopic measurements of liquid-phase adsorption. The influence of the surface polarity on the adsorption process was studied on several materials, e.g. activated carbons, PAF-1, MIL-101(Cr), HKUST-1, and a UiO-67-series. The surface polarity was characterized through the difference in the 1,4-dioxane adsorption uptake from two solvents of opposite polarity, namely n-heptane and N,N-dimethylformamide. An NMR-derived polarity index was defined where the polarity of the MOF corresponds to its affinity to polar substances. It is demonstrated that the structural modifications of MOF materials, which should affect the polarity of these MOFs, are indeed reflected by the polarity index.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Liquid-phase adsorption on MOFs; NMR detection; Polarity index; Surface polarity estimation